The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.5194/acp-3-2147-2003
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of African dust over southern Italy

Abstract: Abstract. Dust samples from rainfall residues have been collected in southeast Italy (40 • 20 N, 18 • 6 E) during dust outbreaks occurred from April to June 2002 to characterize morphological and elemental particle composition by different techniques, and investigate the dependence of particle properties on source regions. Four-day analytical back trajectories and satellite images have been used to infer source regions of the investigated dust samples.It has been found that the TOMS absorbing aerosol index wa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
1
6

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(66 citation statements)
references
References 42 publications
(57 reference statements)
6
53
1
6
Order By: Relevance
“…Furthermore, these particles often have rounded morphologies or chamfered edges, and consist mainly of clay minerals (smectite, kaolinite and illite/mica in variable proportions) and quartz, which are the main components of atmospheric Saharan dust (e.g. Krueger et al, 2004;Brooks et al, 2005;Coz et al, 2009;. Particularly, on these dates the highest amounts of quartz were detected (Figs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, these particles often have rounded morphologies or chamfered edges, and consist mainly of clay minerals (smectite, kaolinite and illite/mica in variable proportions) and quartz, which are the main components of atmospheric Saharan dust (e.g. Krueger et al, 2004;Brooks et al, 2005;Coz et al, 2009;. Particularly, on these dates the highest amounts of quartz were detected (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Al / Si ratios > 0.3 are generally considered indicators of desert dust (Molinaroli, 1996;Guerzoni et al, 1997;Blanco et al, 2003;Kandler et al, 2007;Matassoni et al, 2011), however Coude-Gaussen et al (1987) have already found that the Al / Si ratio can vary with particle size. They noted that finest fractions have an Al / Si ratio significantly lower than that of mean aerosols, with values below 0.3, due to larger amounts of quartz.…”
Section: Discussionmentioning
confidence: 99%
“…Single particle analysis of mineral dust employing SEM-EDXS analysis is basically qualitative because of the irregular shape and wide size range of dust particles (Blanco et al, 2003;Kandler et al, 2007;Fletcher et al, 2011). In addition, the dust particles are mostly the agglomerates of subgrains of wide-ranging mineralogy and size in varying ratios.…”
Section: Dust Samples and Methodsmentioning
confidence: 99%
“…Desert dust aerosols are mainly composed of varying shares of illite, kaolinite and montmorillonite (Kumai, 1961;Kumai and Francis, 1962;O'Hara et al, 2006;Zimmermann et al, 2008;Chudnovsky et al, 2009) depending on the source region (Avila et al, 1997;Ganor, 1991;Blanco et al, 2003;Moreno et al, 2006). These clay minerals have frequently been used as mineral dust surrogates in ice freezing experiments and their ability to act as IN is well established.…”
Section: Pinti Et Al: Ice Nucleation Efficiency Of Clay Mineralsmentioning
confidence: 99%